Utilization of Red Dragon Fruit (Hylocereus polyrhizus) as an Alternative Dye for Threadworm Eggs (Ascaris lumbricoides) - Desti Erfiana; Etiek Nurhayati; Gervacia Jenny Ratnawaty (Borneo Scientific Publishing, 2025)
The red dragon fruit (Hylocereus polyrhizus) contains a pigment called anthocyanin, which gives it its red color and has the potential to be used as a natural dye. In laboratory microscopic preparations, eosin is used as a standard dye. Natural dyes have the advantage of not causing negative effects like cancer or environmental damage. This study aimed to examine the potential of red dragon fruit (Hylocereus polyrhizus) as an alternative dye for the examination of Ascaris lumbricoides eggs. The study design used was static group comparison, with local red dragon fruit samples from Pontianak Tenggara District. Laboratory examination methods involved direct microscopic observation using a 2% eosin control. In this study, the juice from both the skin and flesh of the red dragon fruit was extracted and prepared in solutions of 80%, 90%, and 100% concentrations with four replications. The results showed that the skin of the red dragon fruit at concentrations of 80%, 90%, and 100% was not suitable for coloring the microscopic preparation for observing worm eggs. However, the juice from the flesh of the red dragon fruit at concentrations of 80%, 90%, and 100% could color the microscopic preparations, and the Ascaris lumbricoides eggs could be identified. At the 80% concentration of red dragon fruit flesh, the average score was 2, indicating low contrast background, weak color absorption by the eggs, and unclear egg details. At 90% and 100% concentrations, the average score was 3, indicating a clear contrast background, good color absorption by the eggs, and clear egg detail, similar to eosin 2% staining. This study concludes that the skin of red dragon fruit cannot be used for staining microscopic preparations, while the flesh of red dragon fruit can be used for staining Ascaris lumbricoides eggs, with optimal concentrations of 90% and 100%.